Playing to Strength : Growth Strategy for Small Agrarian Economies in Africa - Yusuf, Shahid; Kumar, Praveen (World Bank, Washington, DC, 2018)
With urban industrialization on the scale achieved by East Asian economies looking increasingly less plausible, small economies in Africa need an alternative strategic approach to long-term growth. The purpose of this paper is to identify a growth strategy with the greatest potential for small, landlocked economies in East Africa. The paper uses Malawi, Rwanda, and Uganda as case studies to explore the potential for growth in agriculture, manufacturing, and tourism in these countries. The paper marshals extensive reasoning that while the manufacturing sector and exports of light labor or resource intensive manufactures could contribute a fraction of aggregate growth, it is agriculture, agribusiness, and services that will contribute the lion’s share because of an unprecedented convergence of technologies. Industrialized agriculture and agri-business could enable these countries to sustain rapid growth even in the face of climate change. Malawi, Rwanda, and Uganda, with some trying, can accelerate their convergence to the technological frontier to take full advantage of this promise. Undoubtedly, there are obstacles to transferring the advanced technologies wholesale to East Africa, but their eventual assimilation is a must and the removal of hurdles needs to be addressed. Extracting the maximum growth mileage will require policy action on multiple fronts.